On Calliandra and Afrocalliandra (Fabaceae-Caesalpinioideae) - Thulin, Mats (Phytotaxa, 2023)
The history of the genus Calliandra is reviewed, with particular reference to the two African species C. gilbertii and C. redacta. These species have been segregated as Afrocalliandra, based on proposed differences from a neotropical Calliandra. The stated differences are acalymmate, 7-celled (versus calymmate, 8-celled) polyads, presence (versus absence) of extrafloral nectaries, and presence (versus absence) of spines or thorns. A scrutiny of these claims shows that neither number of cells in the polyads, nor extrafloral nectaries, nor armature can be used to separate the two African species from the rest of the genus. The only remaining difference is the acalymmate polyads, a plesiomorphic state among mimosoids. On the contrary, a circumscription of Calliandra that includes also the two African species is, apart from being robustly supported by molecular data, also very strongly supported morphologically by 8-celled asymmetrical polyads with tail cells provided with viscin bodies (which are unique among legumes), by expanded stigmas with a wide area of polyad receptivity (which are unique among mimosoids), and by sagittate, petiolate and persistent cotyledons. A return to a circumscription of Calliandra that includes also the two African species is therefore proposed. Calliandra is subdivided into subg. Calliandra, with ca. 140 species in the Neotropics, and subg. Afrocalliandra, comb. et stat. nov., with C. gilbertii in Somalia and Kenya, and C. redacta in South Africa.